Pengenalan “Math Games” Untuk Meningkatkan Keterampilan Operasi Hitung di Sekolah Dasar - Fransiska Yunitai Litau; Kristini Sinisuka; Nurlaili Afsarii Tanjung; Ummi iIfroh; Irma Novia Sari (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
Currently, games are ini great demand among the public as a means of entertaiment from young people to older people. There are many kinds of games, from onlinr suc as shooting gemes to offline one such as educational gemes. The inclusion of games in the learning process creates a pleasant atmosphere because the cild can control the seed of leaning according to his abilities. Creating a Math Games Bsed Counting Operations Learning Game Application for Elementry School Children aims to creat educational games using the Math Games application and provide an educational side. The result of making this game is a game application that is used as a medium for learning aritmetic operations. This game ca later elp students to make it easier to learn mathematics, especially in tems of basic arithmetic operations.